Composition-driven phase evolution and piezoelectric properties of (1−x)(K0.48Na0.52)0.96Li0.04Nb0.95Sb0.05O3−xBi0.5 (Na0.84K0.16)0.48Ba0.02ZrO3 lead-free ceramics. (13th September 2019) - Yu, Yungang; Li, Jingchuan; Dai, Xiaowei; Yi, Yunhe; Pan, Yongqi; He, Caiwang; Liu, Yunyi; Liu, Xiaokui; Chen, Yi
Abstract: In this study, we investigated the correlation between the phase structure, electrical properties and composition of lead-free (1- x )(K0.48 Na0.52 )0.96 Li0.04 Nb0.95 Sb0.05 O3 - x Bi0.5 (Na0.84 K0.16 )0.48 Ba0.02 ZrO3 ceramics, which were prepared by a normal oxide sintering method. X-ray diffraction analysis revealed that all the studied compositions had a pure perovskite structure. Meanwhile, the structural evolution with composition was researched by combining the x-ray diffraction results with the temperature-dependent dielectric data, and a rhombohedral-tetragonal phase boundary was identified to exist in x  = 0.01 to 0.05. Additionally, the grain size of the ceramics was found to gradually decrease with the increase of x, due to the inhibition effect of added Bi 3+, Ba 2+ and Zr 4+ ions on the growing of the grains during sintering process. The ceramics exhibited the optimal piezoelectric properties at compositions near the phase boundary, with the highest piezoelectric constant d 33 and the largest planar electromechanical coupling coefficient k p of 262 pC/N and 0.42, respectively.